Boxes of Poison: Baroque Technique as Antidote to Simple Views of Literacy. (September 2016) - Burnett, Cathy; Merchant, Guy
Rich and complex meaning making experiences, such as those associated with virtual play, sit uneasily with the view of literacy reflected in and sustained by current systems of accountability in education. This article develops a baroque perspective as a way of destabilizing the "regime of truth" associated with simple models of literacy—models that have emerged through educational reform. Building on post-structural approaches, we suggest that a baroque sensibility can help assert the messiness of educational experience and the contingent nature of meaning making that lie at the heart of literacy and learning. We draw on six techniques of the baroque exemplifying their use in an original methodological approach that we call "stacking stories." These stories offer different accounts of actions and interactions in and around a virtual world visited by 9- and 10-year-old children in a U.K. classroom. The stories, together with the gaps, contradictions, continuities, and discontinuities between them, read together through a baroque lens, trouble the taken-for-granted. They evoke the affective intensities produced through interactions between body, text, and place as they infuse each other in multiple acts of meaning making. This baroque approach disturbs ways in which meanings are represented in both research and practice adding to post-structural accounts that foreground multiplicity and complexity. We suggest that such an approach provokes generous, ebullient, and vivid accounts of literacy that are elided by simple models of literacy.